1991
DOI: 10.2307/3431196
|View full text |Cite|
|
Sign up to set email alerts
|

Sequential Measurements of Bone Lead Content by L X-Ray Fluorescence in CaNa 2 EDTA-Treated Lead-Toxic Children

Abstract: With the development of L X-ray fluorescence (LXRF) to measure cortical bone lead directly, safely, rapidly, and noninvasively, the present study was undertaken to a) evaluate LXRF as a possible replacement for the CaNa2EDTA test; b) quantify lead in tibial cortical bones of mildly to moderately lead-toxic children before treatment; and c) quantify lead in tibial cortical bones of lead-toxic children sequentially following one to two courses of chelation therapy. The clinical research design was based upon a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…For a given OTT, the factor by which the observed counts are scaled to adjust for the effects of attenuation, e −µ , was calculated for 2-8 mm of 'skin' of µ = 0.475 mm −1 and 0.45 mm −1 per Wielopolski et al (1989) and Rosen et al (1989Rosen et al ( , 1991aRosen et al ( , 1991bRosen et al ( , 1993, respectively. In order to account for skin and adipose separately, the degree of attenuation was calculated for skin thicknesses of 2 and 3 mm in combination with adipose thicknesses of 1-6 mm; i.e.…”
Section: Correcting For Attenuation In Lxrfmentioning
confidence: 99%
“…For a given OTT, the factor by which the observed counts are scaled to adjust for the effects of attenuation, e −µ , was calculated for 2-8 mm of 'skin' of µ = 0.475 mm −1 and 0.45 mm −1 per Wielopolski et al (1989) and Rosen et al (1989Rosen et al ( , 1991aRosen et al ( , 1991bRosen et al ( , 1993, respectively. In order to account for skin and adipose separately, the degree of attenuation was calculated for skin thicknesses of 2 and 3 mm in combination with adipose thicknesses of 1-6 mm; i.e.…”
Section: Correcting For Attenuation In Lxrfmentioning
confidence: 99%
“…The L XRF system was used in a number of studies, particularly of childhood Pb exposure (Rosen et al 1989, Rosen et al 1991. The researchers performing this work suggested that the then current levels of action based on a blood Pb level of 25 µg Pb dl −1 for childhood Pb poisoning in the U.S.A. were too high.…”
Section: Methodsmentioning
confidence: 99%
“…En investigaciones llevadas a cabo recientemente se han destacado los peligros potenciales que representan las fuentes endógenas de plomo (depósitos óseos), especialmente en poblaciones con una historia de exposición crónica y, por consiguiente, con gran riesgo de movilización de metales tóxicos almacenados en el hueso en situaciones fisiopatológicas que aumentan la resorción ósea. [10][11][12][13][14][15] El plomo tiene efectos tóxicos en muchos órganos, sistemas y procesos fisiológicos, incluyendo el desarrollo de la línea roja hemática, los riñones, el sistema cardiovascular, el aparato reproductor y, problamente el aspecto de mayor gravedad, el desarrollo del sistema nervioso central. La naturaleza de las manifestaciones de toxicidad depende no sólo de la magnitud de la exposición sino también de las características de la persona expuesta; la neurotoxicidad del plomo es más crítica para el feto en desarrollo y el niño en crecimiento que para los adultos.…”
Section: Introductionunclassified